ANALISIS ECONOMIC ORDER QUANTITY PADA PT. ROYAL COCONUT KAWANGKOAN, KECAMATAN KALAWAT, SULAWESI UTARA - Geraldy Tamamengka; Jemmry R Winokan (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2023)
PT. Royal Coconut Kawangkoan is a producer of Dessicated Coconut with a productioncapacity of 20,000 Kg of flour per day, supported by 450 employees. Coconut flourproducts (Desiccated Coconut) produced are coconuts of the Cocos Nucifera type. Theproblems found in this company are that the company does not determine the optimalamount of raw material inventory, the amount of safety stock, and at which point thecompany must order raw materials again. Therefore, in this study, the authors attempt tocalculate the optimal amount of inventory by using the Economic Order Quantity (EOQ)calculation method, as well as calculating the safe stock (Safety Stock) and Reorder Point(RoP) at PT. Royal Coconut Kawangkoan, Kalawat District, North Minahasa Regency.